Foam based synthesis of metal carbonates: establishing the role of spatial confinement for obtaining interesting morphologies - Bala, Tanushree; Sanyal, Ambarish; Pant, Jayashree; Bhagavatula L. V. Prasad (Journal of Computational and Theoretical Nanoscience, 2012)
The crystallization of different carbonates namely lead carbonate, cadmium carbonate and strontium carbonate in aqueous foam stabilized by the surfactant sodium dodecyl sulphate (SDS) by a method of cation entrapment is described. Reaction of ammonium carbonate with the respective cations electrostatically entrapped in the foam results in the formation of minerals, possibly in the Plateau border and Plateau junction regions of the foam. The unusual morphology of the crystals obtained from foam based synthetic method as compared to the crystals prepared in aqueous solution shows the utility of the template for the growth of crystals with an unusual morphology due to constrained environment. The materials are well characterized using TEM, SEM, EDAX and FTIR techniques. The large interfacial area of the liquid lamellae in the foam provides a striking possibility for the large-scale synthesis for not only minerals but also other nanoscale materials.